2021
DOI: 10.1093/cid/ciab306
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of In-Person Primary and Secondary School Instruction on County-Level Severe Acute Respiratory Syndrome Coronavirus 2 Spread in Indiana

Abstract: Objective To determine the county-level effect of in-person primary and secondary school reopening on daily cases of SARS-CoV-2 in Indiana. Methods This is a county-level population-based study using a panel data regression analysis of the proportion of in-person learning to evaluate an association with community-wide daily new SARS-CoV-2 cases. The study period was July 12-October 6, 2020. We included 73 out of 92 (79.3%) In… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 15 publications
(9 reference statements)
1
5
0
Order By: Relevance
“…This study sought to build a more rigorous approach to examining the association between school reopenings and COVID-19 community transmission early in the pandemic by addressing limitations related to comparison groups, confounding of other cooccurring mitigation policies, or insufficient geographic samples. With a highly sophisticated matched design with multiple sensitivity analyses inclusive of enriched data on school and community factors, this study affirms findings of prior studies that detected a positive association between in-person school reopenings and community transmission . That this increase was fairly small may suggest that that adherence to mitigation strategies within schools that resumed in-person education might have been sufficient to narrow the difference in community case incidence between schools that reopened in-person vs virtually.…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…This study sought to build a more rigorous approach to examining the association between school reopenings and COVID-19 community transmission early in the pandemic by addressing limitations related to comparison groups, confounding of other cooccurring mitigation policies, or insufficient geographic samples. With a highly sophisticated matched design with multiple sensitivity analyses inclusive of enriched data on school and community factors, this study affirms findings of prior studies that detected a positive association between in-person school reopenings and community transmission . That this increase was fairly small may suggest that that adherence to mitigation strategies within schools that resumed in-person education might have been sufficient to narrow the difference in community case incidence between schools that reopened in-person vs virtually.…”
Section: Discussionsupporting
confidence: 80%
“…Moreover, the study sample is heavily weighted by the experience within the US South during this period. The reason is 2-fold: (1) summer and fall 2020 in-person school reopenings disproportionately occurred in southern states and (2) the analysis focused on single-district counties to ensure clean ascertainment of the school exposure context at the county-level. While the selection of single district counties represents a methodologic strength in reducing mismeasurement of exposures (opening dates, school safety protocols, sports initiation), it contributed to geographic skew in the study sample, as single-district counties are also more likely to be found in southern states.…”
Section: Limitationsmentioning
confidence: 99%
See 2 more Smart Citations
“…If children and school staff become infected at school, these transmissions may lead to subsequent transmissions to family members and other contacts, potentially resulting in increases in community transmission of SARS-CoV-2. Recently published studies about the impact of school mode on community transmission from Indiana, Texas and other states found conflicting results [10][11][12] , with some analyses suggesting substantial increases…”
mentioning
confidence: 99%